Population of Apogonia cribricollis in oil palm plantation: a case study in Felcra Paya Jenuang / Nur Syafiq Syazzany Abd Rahim - Abd Rahim, Nur Syafiq Syazzany (Faculty of Plantation and Agrotechnology, 2019)
A study was done at Felcra Paya Jenuang on 25th July until 14th August of 2018 regarding population of Apogonia cribricollis. The objectives of the study were to determine the fluctuation of Apogonia cribricollis population on different sampling time and to determine its number on different type of traps. It was expected that different sampling time will result in different number of Apogonia cribricollis’s population while yellow pan trap was expected to have more effective result in trapping Apogonia cribricollis as compare to manual method. Previous studies have shown them as nocturnal insect with eating behavior of biting, cutting and holding their food. The approaches used on field included usage of yellow pan traps filled with soapy water and manual method such as sweeping net. Measures were taken to ensure the uniformity of sampling time. The study area was divided into 10 strata and these approaches were applied on 4 chosen strata. The results showed no significant difference between different sampling date while there is significant difference among the different approaches used in trapping Apogonia cribricollis. This initial hypothesis of different sampling time resulting in different number of Apogonia cribricollis was rejected while expectation of yellow pan trap resulting in higher number of Apogonia cribricollis was accepted. This can be due to their characteristic of nocturnal insects, placement of trap and changes of weather during sampling period. One-way Anova analysis has shown (F=2.273, df=5,138 & P>0.01) for different sampling date and unpaired t-test has shown (F=121.194, df=142,71.000 & P<0.01) for different type of traps used. Presence of Apogonia cribricollis in study area has not exceeded the economic threshold level therefore no corrective measure was required, and prevention methods were suggested.